Data from: Science-graphic art partnerships to increase research impact - Khoury, Colin K.; Kisel, Yael; Kantar, Michael B.; Barber, Ellie; Ricciardi, Vincent; Klirs, Carni; Kucera, Leah; Mehrabi, Zia; Johnson, Nathanael; Klabin, Simone; Valiño, Álvaro; Nowakowski, Kelsey; et al. (Dryad Digital Repository, 2019)
Graphics are becoming increasingly important for scientists to effectively communicate their findings to broad audiences, but most researchers lack expertise in visual media. We suggest collaboration between scientists and graphic designers as a way forward and discuss the results of a pilot project to test this type of collaboration.